The impact of physical exercise interventions on social, behavioral, and motor skills in children with autism: a systematic review and meta-analysis of randomized controlled trials - Wang, YanAn; Qian, Guoping; Mao, Sujie; Zhang, Shikun (Frontiers in Pediatrics, 2025)
BackgroundAutism Spectrum Disorder (ASD) is a neurodevelopmental disorder characterized by social impairments, sensory processing issues, repetitive behavior patterns, motor abnormalities, and executive function impairments.ObjectiveTo systematically review and meta-analyze the effects of various exercise modalities on flexibility and cognitive control, social skills, behavioral problems, motor skills, and coordination in children with ASD, providing scientific evidence for clinical practice to guide effective exercise interventions for children with ASD.MethodsLiterature searches were conducted in PubMed, EMbase, Cochrane Library, EBSCOhost, and Web of Science databases, covering the period from database inception to February 15, 2024. Inclusion criteria included studies involving children with ASD, any form of exercise intervention, reporting at least one ASD-related outcome, and designed as randomized controlled trials (RCTs) or quasi-experimental studies. Exclusion criteria included reviews, conference abstracts, commentary articles, and studies lacking sufficient statistical data for meta-analysis. Study quality was assessed using the PEDro scale. Effect sizes were calculated using standardized mean differences (SMD). Heterogeneity was assessed with the I2 statistic. Multiple subgroup analyses were conducted, and publication bias was evaluated using Begg's Test and Egger's Test.Results23 RCTs were included in this study, showing positive effects of exercise interventions in various domains.Upper grade students showed significant improvement in flexibility and cognitive control (SMD = −0.282, p = 0.161). Lower grade children showed the most significant improvement in motor skills and coordination (SMD = 0.475, p = 0.043). Preschool children showed significant enhancement in social skills (SMD = 0.312, p = 0.041). Behavioral problems improved significantly across all age groups (SMD = −0.674, p < 0.001). Martial arts and ball games were particularly effective in enhancing these domains, and appropriate periodic exercise interventions effectively improved various abilities in children with ASD. Results varied across different ages and intervention types.ConclusionExercise interventions significantly improve flexibility, cognitive control, motor skills, coordination, social skills, and behavioral problems in children with ASD. This study supports exercise interventions as an effective method to enhance multiple abilities in children with ASD and emphasizes the importance of designing personalized intervention programs tailored to different ages and needs. Future research should focus on larger sample sizes and long-term follow-ups to confirm the sustainability and generalizability of intervention effects.